Seeking and avoiding contact with Muslims at a Hijab Stall: Evidence for multilayer, multi‐determined solidarity, courage, apathy, and moral outrage. (22nd June 2021) - Paolini, Stefania; Azam, Fatima; Harwood, Jake; Mackiewicz, Matylda; Hewstone, Miles
Abstract : Intergroup contact is key to social cohesion, yet psychological barriers block engagement with diversity even when contact opportunities are abundant. We lack an advanced understanding of contact seeking because intergroup contact is often an independent variable in research, and studies on contact seeking have favoured experimental probing of selected factors or measured only broad behavioural intentions. This research carried out the first ecological tests of a novel multilayer‐multivariate framework to contact seeking/avoiding. These tests were centred on a Muslim‐led community contact‐based initiative with visible support from local authorities following a terrorist attack. Non‐Muslim Australian women ( N  = 1, 347) contributed field data on their situated contact motivations, choices, and attendance at an intercultural educational stall; many ( N =  559) completed a profiling test battery. Among those who responded to the initiative invite, the rate of taking up the high‐salience contact opportunity in this heated setting was high and reflected multiple approach/avoidance motivations. Contact seeking/avoiding was not just allophilia/prejudice; it presented as new typologies of politicized solidarity, courage, apathy, and moral outrage. While intergroup predictors were significant across all profiling analyses, intrapersonal and interpersonal predictors also regularly contributed to explain variance in non‐Muslims' contact motivations and choices, confirming their multilayer‐multivariate nature.